INVARIANT FILTERING RESULTS FOR WIDE BAND NOISE DRIVEN SIGNAL SYSTEMS - Bashirov, A. E.; Abuassba, K. (Turkic World Mathematical Soc, 2018)
Filtering of wide band noise driven systems accounts the following problem. Given an autocovariance function, there are infinitely many wide band noise processes, which have this autocovariance function. Each of them produces its own best estimate. The problem is a selection of the best one of these best estimates. A similar problem arises in control theory as a selection of optimal one of the optimal controls. In this paper we investigate this problem for a wide class of wide band noises. It is proved that in the case of independent wide band and white noises corrupting, respectively, the signal and observations, the best estimates and the optimal controls in the linear filtering and LQG problems are independent of the respective wide band noises. We present a complete set of formulae for the best estimate and, respectively, for the optimal control in terms of the system parameters and autocovariance function of the wide band noise disturbing the signal system.
Keywords: Wide band noise; white noise; Kalman filtering; LQG problem